Inoculation of soil with cadmium-resistant bacteria enhances cadmium phytoextraction by Vetiveria nemoralis and Ocimum gratissimum - Khonsue, Napakan; Kittisuwan, Kitti; Kumsopa, Acharaporn; Tawinteung, Nukoon; Prapagdee, Benjaphorn (My University, 2013)
Two cadmium-resistant bacteria, Ralstonia sp. TAK1 and Arthrobacter sp. TM6, produced exopolymers that promoted cadmium solubilization in contaminated soil. The enhancement of cadmium uptake and accumulation in amonocot (Vetiveria nemoralis, vetiver grass) and a dicot (Ocimum gratissimum, African basil) was investigated in a greenhouse study. Compared with the uninoculated control, Ralstonia sp. TAK1 and Arthrobacter sp. TM6 increased cadmium accumulation in the roots and shoots of V. nemoralis. These cadmium-resistant bacteria increased the cadmium content of whole V. nemoralis plants similarly to ethylenediaminetetraacetic acid (EDTA) treatment alone. In contrast, only Arthrobacter sp. TM6 enhanced cadmium accumulation in the roots and shoots of O. gratissimum. The highest cadmium content of wholeO. gratissimum plants was observed when the plant was treated with EDTA following treatment with Arthrobacter sp. TM6. The phytoextraction coefficient and translocation factor (TF) of bacteria-inoculated V. nemoralis were higher than those of O. gratissimum. Arthrobacter sp. TM6 increased the phytoextraction coefficients and TFs in V. nemoralis and O. gratissimum. These results indicate that Arthrobacter sp. TM6 and both tested plant species promote cadmium phytoextraction in contaminated soil. © Springer Science+Business Media Dordrecht 2013.
Keywords: African basil; Cadmium-contaminated soil; Cadmium-resistant bacteria .Vetiver grass; Phytoextraction